If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 1 = 6x + -7 Reorder the terms: 1 + 4x = 6x + -7 Reorder the terms: 1 + 4x = -7 + 6x Solving 1 + 4x = -7 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 1 + 4x + -6x = -7 + 6x + -6x Combine like terms: 4x + -6x = -2x 1 + -2x = -7 + 6x + -6x Combine like terms: 6x + -6x = 0 1 + -2x = -7 + 0 1 + -2x = -7 Add '-1' to each side of the equation. 1 + -1 + -2x = -7 + -1 Combine like terms: 1 + -1 = 0 0 + -2x = -7 + -1 -2x = -7 + -1 Combine like terms: -7 + -1 = -8 -2x = -8 Divide each side by '-2'. x = 4 Simplifying x = 4
| 2x+8-15=45 | | 2x+8-25=45 | | 2(4n+8)= | | (5)10-(5)13= | | -6x=80 | | a-z=-5(39-a)-3 | | 171-3x=24x+18 | | x^2-16x+64=3 | | x=2*x-4 | | x^2+2x+1=49 | | y=30+11y | | 3x+2b=x+8 | | x=x-2*2x-4 | | 9x^2-14x-8=0 | | x^2+20x-3=0 | | 56753366x=786556 | | 9x^2+65x+14=0 | | a=12a-44 | | x=(x-2)*(2x-4) | | 5x^2+38x+21=0 | | x^2+18x+90=0 | | x^2+18+90=0 | | 20x+35=0 | | 6x+20=3x+11 | | x=x-2*(4) | | x=4*(x-2) | | x=2*x+1-(2*2+1) | | (x-7)(2x+9)=0 | | x=x-2*(2) | | x=2*x+1-2*2+1 | | 9X-22=32 | | 5(x-2)-7(x+1)=9(3-2x) |